Impact of urbanization on health, vulnerability and child health outcomes in Malaysia - Sivadas, Sudha (2019)
Urbanisation is inevitable, as the world population continues to increase and the urban population rises more rapidly than the rural population This thesis aims to decipher the impact of urbanisation in Malaysia by presenting empirical evidence and contributing to existing literature on the impact on non-communicable diseases (NCDs) prevalence and related health risks in urban areas; on the impact on socioeconomic outcomes for the vulnerable groups; and the impact on child health outcomes, especially those belonging to vulnerable households. The first objective is to establish if the urban population is more exposed to NCDs and the health risks related to these diseases. Usually, studies regarding the prevalence of diseases are often viewed from a health care perspective, in terms of demand, accessibility and quality of services. However, this research provides a socio-economic angle, in that it reviews the prevalence of NCDs in the spatial, lifestyle and economic context. Results show, based on the Probit method, that demographic factors are important determinants of NCD prevalence for both 2006 and 2015. Socioeconomic factors are increasingly important, as reflected by the 2015 results. The physical activity variable results show active individuals are more prone to NCDs. Urbanisation’s role has a mixed outcome. Although the NCDs as a whole showed urban to have a negative impact, the results for Diabetes mellitus (DM) were positive for both 2006 and 2015. This suggests that urban folks were more likely to have DM, perhaps due to their lifestyle choices compared to those living in rural areas. The second objective is to establish the socioeconomic outcomes for the vulnerable groups, especially the urban vulnerable. Based on Ordinary Least Square estimates, the urban vulnerable groups are faring poorly compared to the general vulnerable groups, and this applies even at the subcategories of single parents and the elderly. Vulnerable single parents and vulnerable elderly are worse-off in urban compared to in rural. However, it is noteworthy that the lot of urban vulnerable groups has improved between 2006 and 2015. Education, often deemed a tool for upward social mobility, is pivotal in improving the incomes of vulnerable groups. Financial protection too is beneficial in improving the vulnerable groups earning likelihood. Next, the third object on child health outcomes, establishing their health outcome, especially in terms of nutrition amongst vulnerable household children. Focus here is malnutrition, both under-nutrition and over-nutrition, among urban children aged between 5 and 17 years of age. Through the Probit method, findings show that demographic factors are significant for child malnutrition prevalence and that vulnerable groups are more likely to have underweight children compared to the bottom 40 category. Overall, the main findings show that urbanisation impacts NCD prevalence, vulnerable groups and child health outcomes. However, the difference is increasingly indistinct, where rural folks are also increasingly exposed to urban conditions. For NCDs, generally the urban factor was not significant except for DM. Vulnerable groups in urban had a poorer quality of life, even at the disaggregated sub-population level. The child health outcomes show that urban households were less likely to have overweight children, but children in vulnerable households, including in urban areas, are more likely to be underweight. Therefore, policies and action plans should be explicitly drafted at the disaggregated sub-populations within the urban area, facilitating targeted resource planning and deployment that ultimately delivers better outcomes. Firstly, what constitutes an urban area must be reviewed, to ensure it is current and relevant today. Next, the vulnerable definition must be revised to be more dynamic and robust, reflecting the multi-dimensional nature of the population at risk of becoming poor. A more explicit recommendation is to implement community-based health education and awareness programs targeting local population needs, that will further augment prevention efforts. will be more effective in attaining health outcomes. Similarly, efforts to boost enforcement, particularly in the realm of child malnutrition, will ensure the existing relevant policies and guidelines attain its intended outcomes.